MicroRNAs in solid cancer : from biomarkers to therapeutic targets - Slabý, Ondřej (Nova Science, 2012)
MiRNA is an extremely fast growing field, and miRNA knowledge is now believed to be a pivotal element of cancer biology. It is already evident that the discovery of miRNA has created a paradigm shift in post-genomics biology, not only for scientists accustomed to traditional central dogma of molecular biology but also for researchers studying human diseases and accustomed to traditional genetics approach of studying one gene at the time. This book provides an introduction to the basic principles of miRNA biology, overview of miRNA significance in the hallmarks of cancer, experimental techniques used in miRNA research, and in special part - miRNAs importance in wide range of solid cancers with a special focus on its potential usage in molecular pathology, predictive oncology or as a novel therapeutic targets.
DNA and RNA: properties and modifications, functions and interactions, recommendations and applications
Cancer etiology, diagnosis and treatments
Keywords: regulace genové exprese u nádorů; biologie; Gene Expression Regulation, Neoplastic; Neoplasms by Site; genetika, lékařská genetika; MicroRNAs; regulace genové exprese; Biomarkers, Tumor; Gene Expression Regulation; nádory podle lokalizace; nádorové biomarkery; Polymorphism, Genetic; Molecular Biology; mikro RNA; polymorfismus genetický; onkologie; molekulární biologie